Workplace stress among healthcare workers in Kut city, Iraq, 2020 - Fatima Haran Deham,; Alaa Kadhim Jasim,; Khalied Yassen Zakair, (Journal of the Pakistan Medical Association, 2023)
Objective: To identify workplace stress in healthcare workers. Method: The cross-sectional, descriptive study was conducted at Al-Kut and Al-Karamah hospitals in Kut, Iraq, from October 2019 to March 2020, and comprised health professionals regardless of age and gender. Data was collected through a pilot-tested questionnaire which was validated by a panel of experts. Data was analysed using SPSS 25. Results: Of the 266 subjects, 133(50%) were from each of the two hospitals. Overall, there were 156(58.6%) females and 110(41.4%) males. There were 195(73.3%) subjects aged <30 years, 40(15%) aged 31-40 years and 31(11.7%) aged >40 years (p=0.625). There were 19(7.1%) physicians 72(27.1%) nurses, 88(33.1%) technicians and 87(32.7%) other healthcare workers. Stress was found in 20(7.5%) subjects; 13(65%) in Al-Karamah Hospital and 7(35%) in Al-Kut Hospital (p=0.245). Conclusion: The prevalence of stress was low among the health workers studied. Keywords: Stress, Ergonomics, Healthcare, Workers, Workplace.